Evaluation of the Implementation of the Adiwiyata Program in Enhancing Environmental Awareness: A Case Study of SMAN 2 Sangatta Utara - Teddy Artotari; Berlian Elva; Novi Indri (Journal of Education Innovation and Curriculum Development, 2023)
The Adiwiyata Program is a national initiative aimed at fostering environmental awareness and sustainable practices in Indonesian schools. This research focuses on evaluating the implementation of the program at SMAN 2 Sangatta Utara, exploring its effectiveness in promoting environmental education and instilling eco-conscious behaviors among students. A qualitative methodology was employed, including interviews with stakeholders, field observations, and analysis of program-related documentation. The findings reveal that the program has successfully integrated environmental values into the school's curriculum and extracurricular activities, resulting in increased student participation in sustainable practices such as waste management, tree planting, and water conservation. However, challenges such as limited funding, inconsistent stakeholder commitment, and gaps in program monitoring were identified. This study highlights the importance of evaluating such initiatives to enhance their impact and sustainability. The results offer insights for policymakers and educators on improving environmental education programs and their integration into school curricula. By addressing identified barriers and replicating successful practices, the Adiwiyata Program can serve as a model for achieving broader environmental education goals and fostering a generation of environmentally responsible citizens.